The Vajramahābhairavatantra: Its origins, intertextuality, and transmission - Wenta, A (2020)
This thesis focuses on the Vajramahābhairavatantra, a seminal Buddhist tantra dedicated to the fear-inducing buffalo-headed Buddhist tantric deity Vajrabhairava (rdo rje ’jigs byed). The tantra has survived to us through Sanskrit manuscripts, which have not previously been investigated. My project intends to fulfill this desideratum by providing the first-ever edition of the Sanskrit text of the Vajramahābhairavatantra and by reconstructing its missing parts from the Sampuṭatantra. Apart from the establishment of a critically edited version of the text and the production of an English translation, my thesis studies the contents in the light of relevant sources outside the corpus, such as early Śaiva and Buddhist tantras like the Niśvāsatattvasaṃhitā, the Mañjuśriyamūlakalpa, but also of sources within the corpus, such as the six canonical commentaries on the difficult points of the root-text. My focus on the intertextual relations between the Vajramahābhairavatantra and other early tantras, as well as the close analysis of the tantra’s Indian exegetical tradition that has survived uniquely through the Tibetan canon, the Bstan ’gyur is important for our understanding of the origin and development of the Vajrabhairava cult. While sufficient scholarly attention has been paid to comparatively late milieus, such as the Chinese, Tibetan, and Mongolian instantiations, the early Indian cradle has been neglected. The aim of my thesis is to demonstrate that the Vajrabhairava cult can be located within the cultural framework of early tantric magic, and thus contains elements that point back to an earlier period than what had been assumed so far. Besides uncovering the intertextual and intellectual relationships between Śaiva and Buddhist tantric traditions, my thesis investigates the appropriation and consolidation of the tantra in Tibet, especially through a reconstruction of the lineages that took part in its transmission from India to Tibet in the light of existing Tibetan historiographies. It thus contributes to our understanding of the appropriation of Indic Buddhist traditions on the Tibetan plateau.